MOST COMMON MENTAL DISORDERS AFFECTED IN ADOLESCENTS DURING THE COVID-19 PANDEMIC - Baroni Araujo, Gustavo; Gomes dos Santos, Jordane; Silva Pereira, Paloma; Cesar Pereira da Silva, Júlio; Fernandes de Carvalho Farias, Anderson; Gonçalves dos Santos, Izani; Pereira da Silva, Isaias; da Costa Araújo, Bruna; da Costa Araújo, Paulo; Maria dos Santos da Silva Apolinário, Joelma; de Carvalho Alves , Winícius; Henrique de Sousa Figueiredo, Iaggo (Health and Society, 2022)
Introduction: Since the origin of the COVID-19 pandemic, many consequences have been constantly faced by the population. The threat related to the numbers of contamination, accentuated by catastrophic reports of serious illness or death, added to the scenes shown in the media of hastily built cemeteries and crowded hospitals can have a direct effect on the mental health of the population, generating fear and insecurity. Adolescents, when infected with the coronavirus, have the same clinical symptoms as adults. In this context, when it comes to worsening health, mental health problems and domestic violence were the main predisposing factors that caused damage to well-being, societal characteristics that should influence the individual and collective health of adolescents. Therefore, knowing the relevance of this theme, this study aimed to identify in the literature the characteristics of mental disorders that affect adolescents during the pandemic. Methodology: This is a descriptive, exploratory, integrative literature review, carried out from a bibliographic survey in the following databases: Latin American and Caribbean Literature on Health Sciences (LILACS) and Scientific Electronic Online Library (SCIELO). Results and Discussions: Clinically, adolescents are proposed to develop the same symptoms of mental disorders as adults during the period of isolation. The context of the economic crisis, social isolation and the weakening of health services are related as the main factors that contributed to the development of mental illnesses such as depression, anxiety, self-mutilation and panic syndromes. Final considerations: Therefore, it became evident that the main disorders that affect young people and adolescents during the period of isolation, resulting from the COVID-19 pandemic, are ansiety and depression. In addition, the main causes that trigger such problems are isolation measures and family problems.